Physicochemical and Sensory Characterization of 20 Wild Cacao Genotypes from the Germplasm Bank of the Instituto de Cultivos Tropicales - ICT, Peru - Marilyn Estefany Medina-Ramírez; Enrique Arévalo-Gardini; Cesar Oswaldo Arévalo-Hernández; Oscar Wilfredo Mendieta-Taboada; Virupax Baligar; Dapeng Zhang (Revista Agrotecnológica Amazónica)
Cocoa (Theobroma cacao L.) is a key crop for the Peruvian economy and society, with a wide genetic diversity, especially in the Amazon. However, many wild genotypes have not yet been characterized, limiting their use. This study evaluated 20 wild cacao genotypes from seven river basins in Loreto, Peru, through physical, chemical, and sensory analyses. The samples, from the germplasm bank of the Institute of Tropical Crops (ICT), were analyzed in terms of grain size, moisture, fat, acidity, pH and cadmium. A strong correlation was found between genotypes, with some commercial varieties outperforming commercial varieties in the bean index, suggesting their potential for the chocolate industry. Fat content ranged from 41.6% to 56.9%, within the ideal range for high-quality chocolate, while cadmium levels remained below European limits. The sensory analysis identified well-defined flavor profiles, highlighting the PAS-100, MACH-26 and AYP-1 genotypes for their aromatic complexity. These results underscore the importance of conserving the biodiversity of wild cacao and its potential in the production of premium chocolate, encouraging further studies on its genetic and industrial value.